Up and down the value-added tax asymmetric incidence of a large VAT reform in Portugal - Sousa, Pedro Manuel Tavares de (2020)
This paper assesses the incidence of a large and temporary increase in value-added taxfor Portuguese restaurants and other catering services. In 2012 the tax increased from 13%to 23% and it was brought back down in July of 2016. Combining data on all non-financialfirms in Portugal between 2006 and 2017 we estimate effects upon four agents: workers,firm-owners, suppliers and consumers. Through a Difference-in-Differences strategy wefind that: the tax increase did not harm employees as severely as firm’s margins, leadingemployers to later pocket most of the tax cut benefits. Also, firm-owners pass onto con-sumers around 40% of the VAT increase while the pass-through after the repeal is zero.